2004 Annual Conference Proceedings
DOI: 10.18260/1-2--13390
|View full text |Cite
|
Sign up to set email alerts
|

The Feminist Engineering Classroom: A Vision For Future Educational Interventions

Abstract: In the quest for the gender equalization of the engineering profession, a variety of strategies are being developed and used in daily engineering education practice. Colleges and universities are recruiting girls and women in increasing numbers into the so-called "engineering pipeline" by using camps, special classes, printed and internet-based advertising, and/or "girl-power" media programming to make engineering's image more appealing -for example, as fun, socially useful, and multidisciplinary. Concurrently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…It made me think more critically about the studies I read, my own biases, and how I can design better," said one engineering student. This is consistent with the work of Cech [19] and Pawley [42] and with Evelyn Fox Keller's notion that the myth of STEM objectivity perpetuates exclusion and marginalization. Our findings suggest that an understanding of STEM's non-neutrality is empowering and liberatory for some underrepresented students in engineering, and correlates with their sense of belonging and engineering identity development.…”
Section: Discussionsupporting
confidence: 90%
“…It made me think more critically about the studies I read, my own biases, and how I can design better," said one engineering student. This is consistent with the work of Cech [19] and Pawley [42] and with Evelyn Fox Keller's notion that the myth of STEM objectivity perpetuates exclusion and marginalization. Our findings suggest that an understanding of STEM's non-neutrality is empowering and liberatory for some underrepresented students in engineering, and correlates with their sense of belonging and engineering identity development.…”
Section: Discussionsupporting
confidence: 90%
“…For professional skills (which include teamwork and communication), research indicates that working in small, collaborating groups enhances female STEM students' attitudes and achievements in particular (P. B. Campbell, Jolly, Hoey, & Perlman, 2002;Johnson & Johnson, 1983;Pawley, 2004). These findings raise future research questions: (a) Might females have a different affinity for certain skills than males?…”
Section: Cluster Comparisons For Each Variable Setmentioning
confidence: 99%
“…More than 70% of the STEM faculty at SCU report using lecture as their main form of instruction all or most of the time, as compared to 56% of all the SCU faculty and 51% of all reporting faculty nationwide. Based on these numbers it is likely the students received the prerequisite instruction in a lecture style format, which would have a greater negative impact on the performance of the female students [4], [5]. The inclusion of active pedagogies versus lecture could also account for the significant disparity between the females' pre-and post-concept inventory gains versus the males' gains, with the males scoring 50% higher than the females on the pre-concept inventory but only 7.0% higher on the post.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have reported the importance of collaborative and small-group instruction on the performance and motivation of female students [4], [5]. Female students also indicate stronger frustrations with what they view as poor teaching and are more likely to leave engineering than male counterparts with equivalent GPAs [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation